THE EFFECTIVENESS OF HENIâ€™S DENTAL FLANNEL BOOKâ€ ON INCREASING DENTAL HEALTH CARE AMONG EARLY CHILDHOOD EDUCATION PROGRAM - Widyastuti, Nugraheni; Fatmasari, Diyah; Djamil, Masrifan (Postgraduate Program , Poltekkes Kemenkes Semarang, 2020)
ABSTRACTOne of the factors causing dental caries is the lack of children's knowledge resulting in a lack of awareness of children in maintaining dental hygiene. To increase children's knowledge can be done by promoting dental health through child oral health education and mouth. The use of media is still less effective in health education that has been running, therefore the need for innovation and development is to use media innovation â€œHeniâ€™s Dental Flannel Bookâ€The study aimed to develop of â€œHeniâ€™s Dental Flannel Bookâ€ media as a health education book and the effectiveness â€œHeniâ€™s Dental Flannel Bookâ€ for increasing the dental health care of Early Childhood Education Programs.Research and Development (R & D), there are ten stages of research namely: information gathering, design models, validation expert, revision, product trial (Pre experiment with one group pre-test post-test, a sample of 15 children), revision, application trial (Quasi-experimental with pre-test and post-test nonequivalent control group design, a sample of 20 children in the intervention group and 20 children in the control group, final product revision, production of product. Data were tested using ANOVA, Shapiro Wilk, Wilcoxon test, Mann-Whitney test.The results showed â€œHeniâ€™s Dental Flannel Bookâ€is effective as an effort to increase dental and oral health care for Early Childhood Education Programs as indicated by a p-value<0.001. Children's knowledge is indicated by a p-value<0,000, a child's attitude is indicated by a p-value <0,000. There is a difference in the effectiveness of smart dental books and flipchart in increased dental and oral health care for children with a p-value<0,000.The conclusion is â€œHeniâ€™s Dental Flannel Bookâ€ effectively improve children's knowledge and attitudes.Keywords : children in Early Childhood Education Programs , â€œHeniâ€™s Dental Flannel Bookâ€, dental health care.